Answer:
(8, - 3 )
Step-by-step explanation:
Given the 2 equations
x - y = 11 → (1)
3x + 10y = - 6 → (2)
Multiplying (1) by 10 and adding to (2) will eliminate the y- term
10x - 10y = 110 → (3)
Add (2) and (3) term by term to eliminate y
13x + 0 = 104
13x = 104 ( divide both sides by 13 )
x = 8
Substitute x = 8 into either of the 2 equations and solve for y
Substituting into (2)
3(8) + 10y = - 6
24 + 10y = - 6 ( subtract 24 from both sides )
10y = - 30 ( divide both sides by 10 )
y = - 3
solution is (8, - 3 )